Regional Security Complex in ASEAN: Neutrality and Centrality at Brink in the South China Sea Issue - Arfin Sudirman (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2017)
The South China Sea conflict has been a highly sensitive issue for the last 5 years in ASEAN. China and the US have been using the South China Sea as the “New Cold War Arena” of power and military hegemonic competition in the South East Asia region. This has been a major challenge for ASEAN as the only regional organization in the South East Asia region that has direct in the area must take major role in managing and resolving the dispute peacefully even though ASEAN has no defense pact like NATO. This paper argues that ASEAN, at this moment, must maintain its role as a mediator and independent-negotiator in the region but at the same time apply its principle of gradually adapting with the new international system. This article also suggests that in the future, ASEAN can take a major role in the governance of the South China Sea and the South East Asia region.